The Condition of Coral Reefs in the Waters Around the Banyan Tree Bintan Bintan Regency Riau Islands Province - Satria Putra Anggara; Afrizal Tanjung; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of this research is to know the condition of coral reefs including the live coral cover, the diversity index, the uniformity index, and the dominance index of the waters of Banyan Tree Bintan. This research had been conducted in the waters around Banyan Tree Bintan from September until November 2016. There are three stations with two depth; Angsana House Reef, Rawa Island and Manjin Island. The data of coral reefs were collected by using Underwater Photograph Transect (UPT) method. The result which was analyzed by using CPCe application revealed that the condition of the coral reefs was ranged around 21,88 % to 32,87% which can be classified as poor to moderate category sequentialy. The low number of coral covers was caused by rising sea temperature and coral bleaching. The highest coral cover was located in the Angsana House Reef at a depth of 5 meters in otherwise the lowest one was located in the Rawa island at 2 meters depth. The quality of water such as temperature, salinity, pH, current velocity and the visibility of the research location was good for coral reefs recovery and growth. The diversity index moderate, the uniformity index was low, and the dominance index was ranged from low to moderate level.Keywords: Terumbu Karang, Banyan Tree Bintan, Underwater photograph Transect (UPT), Coral Bleaching.